1988
DOI: 10.1007/bf02549513
|View full text |Cite
|
Sign up to set email alerts
|

Bladder agenesis

Abstract: Agenesis of the bladder is an extremely rare anomaly with only approximately 40 such cases reported in the literature. We report on a 30-year-old female patient who also had right renal agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Bladder agenesis is a rare congenital anomaly in viable infants. Most of the reported cases were from autopsy series of stillbirths with multiple congenital anomalies, because unless the ureters are able to drain to an ectopic location such as the vagina [20,21], which occurred in the two oldest surviving patients reported, bladder agenesis is incompatible with life. In the present animal model, there was complete absence of the bladder, which contrasted with earlier studies by Thompson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder agenesis is a rare congenital anomaly in viable infants. Most of the reported cases were from autopsy series of stillbirths with multiple congenital anomalies, because unless the ureters are able to drain to an ectopic location such as the vagina [20,21], which occurred in the two oldest surviving patients reported, bladder agenesis is incompatible with life. In the present animal model, there was complete absence of the bladder, which contrasted with earlier studies by Thompson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of bladder agenesis and an extensive array of ureteric abnormalities have been reported in the literature [1][2][3]. In bladder hypoplasia, it is believed that inadequate filling with urine results in underdevelopment of the fetal bladder.…”
Section: Discussionmentioning
confidence: 97%
“…The prenatal presentation was due to oligohydramnios, and the definitive diagnosis was after birth. (2) Late presentation: beyond the first year of life, usually with incontinence [ 2 , 3 , 5 , 11 , 15 , 18 , 37 , 40 , 52 , 53 ], urinary tract infection (UTI) [ 1 , 6 , 30 , 34 , 43 ], or both [ 13 , 27 , 30 , 33 , 35 , 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nazer et al’s subject had a low bifurcation of the aorta, and the internal iliac arteries were absent [ 51 ]. Akdas et al found that the subject had an absent right renal artery [ 11 ]. Lastly, an esophageal ring is formed by the left aortic arch and a posteriorly coursing aberrant right subclavian artery [ 46 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation